Spherical partition of road tank subjected to external pressure - Paščenko, Petr (Univerzita Pardubice, 2008)
The thin-walled spherical cap loaded by an external pressure shows a non-linear behavior. This phenomenon is further amplified in the case of the simply supported cap with free radial displacements of the edge. Using normal calculation procedures based on the linear mechanics is not possible here. A detail numerical computational analysis using, for example, the finite element method (FEM) is necessary. In addition to large displacements, non-linear behavior of material is possible to consider. It should also be noted that stability carrying capacity might be considerably influenced by initial imperfections. Using standard procedures for calculations of real spherical caps is possible, however, often quite conservative. The question of the initial imperfection effect on stability of spherical caps is a subject of further research.
Vrchlíková přepážka silniční cisterny zatížená vnějším tlakem
Diaphragma der Kugelhaube des Tankwagens, der mit dem Druck von aussen belastet ist